Two Level War Games: The Domestic Factors that Influence Presidential Decision-Making to Use Force in Minor Conflicts - Nadeau, Paul J. (Tufts Archival Research Center, 2005)
Submitted in partial fulfillment of the degree of Master of Arts in Law and Diplomacy at the Fletcher School of Law and Diplomacy. Abstract: Research that has analyzed presidential decisions to commit to military force have traditionally either focused on international trends or, if considering domestic trends, have generally focused on major conflicts. While certain domestic factors such as economic conditions, in group/out group sociological hypotheses, and presidential popularity may all plausibly apply to the use of force in major conflicts it is more difficult to determine how strongly these might hold up in minor conflicts where the goals and application of force is limited and when there is usually little direct threat to the homeland itself. This paper will look into the domestic influences upon presidential decisions to use force in minor conflicts using the war in Bosnia and Kosovo air campaigns as a case study with additional consideration given to the recent campaign in Libya.